2022
DOI: 10.3389/fvets.2022.981640
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GPR41 attenuated glucose production in propionate-induced bovine hepatocytes

Abstract: Bovine liver mainly utilizes the propionate as a gluconeogenic substrate to synthesize the glucose. However, the mechanism underlying the regulatory effects of propionate on the glucose production in bovine hepatocytes remains less known. Previous studies have demonstrated G protein-coupled receptor 41 (GPR41) as receptors for propionate. We hypothesized that propionate may regulate the glucose production by GPR41 in bovine hepatocytes. Therefore, the aim of the study was to investigate the regulatory effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similar to this, it has been demonstrated that activating GPR41 significantly affects a number of physiological processes, including gluconeogenesis, energy expenditure, and the production of the intestinal PYY [62]. Additionally, several studies have demonstrated that SCFAs can enhance glucose metabolism in adipose, muscle, and liver tissues, thus promoting body homeostasis [63].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 57%
“…Similar to this, it has been demonstrated that activating GPR41 significantly affects a number of physiological processes, including gluconeogenesis, energy expenditure, and the production of the intestinal PYY [62]. Additionally, several studies have demonstrated that SCFAs can enhance glucose metabolism in adipose, muscle, and liver tissues, thus promoting body homeostasis [63].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 57%
“…However, the expression of enzymes that regulate the conversion of propionate to pyruvate, such as ACSS1 , MCEE , PCCA , MMUT , and SUCLG2 , and the expression of key gluconeogenic genes, such as FBP1/2 , were not analyzed in these previous studies. Moreover, the mechanisms underlying the regulatory effect of propionate on the expression of gluconeogenic genes were not elucidated in a large number of previous studies on this topic ( Aiello and Armentano, 1987 ; Lin et al., 2022 ; Zhang et al., 2015 , 2016 ). In the current study, we not only explored the effect of propionate on key transcription factors regulating gluconeogenic genes such as HNF4A , PGC1α , FOXO1 , and CREB but also examined the upstream signaling pathways regulating these transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of specificity, FFAR2 displays a dual coupling through G i/o and pertussis toxin-insensitive G q protein, further influencing cyclic adenosine monophosphate (cAMP), the extracellular signal-regulated protein kinase 1/2 (ERK1/2) cascade, and calcium channels, whereas FFAR3 couples exclusively with the G i/o protein family [ 120 , 121 ]. Both cell surface receptors are detected in a variety of organs beyond the intestine [ 122 , 123 , 124 , 125 ], with expression described in immune cells [ 126 , 127 , 128 ], liver [ 129 , 130 ], and adipose tissue depots [ 131 , 132 , 133 ]. The importance of the hydroxycarboxylic acid receptor HCA2 (GPR109A) and olfactory receptor 78 (OLFR78) as potential SCFA receptors has been less extensively explored [ 133 , 134 ].…”
Section: Scfa Receptor Signalingmentioning
confidence: 99%